RESOURCE ALLOCATION TECHNIQUE WITH GENETIC ALGORITHM IN MIMO-LTE - Rizqi Utami, Amalia
The rapid of technology development are always keep happening nowadays . Third Generation Partnership Project (3GPP) introduced Long Term Evolution (LTE) to follow the improvement of cellular communication. LTE needed setting of radio resources allocation for all user. This allocation should be done accurately to achieve an optimal system in order to get an equal high speed of packet data service. Algorithm of allocation radio resources are needed to achieve an optimal system’s performance. This research simulate resource block to user in down link way using Genetic Algorithm (GA) with Multiple Input Multiple Output (MIMO) antenna configuration. The parameters that measured are performance of average capacity and fairness by using Genetic Algorithm. Condition of channel is raised using CSI (channel state information) that will be used on resource block allocation. The result of simulation showed that the addition n user will affect the average capacity. More amount of user will have smaller average capacity, besides average capacity also affects by the amount of resource block that allocated in Genetic Algorithm. More resource block will increase the average capacity